COMPENSATION FOR HOME MORTGAGE CREDIT TRANSFER BY THE DEBTOR WITHOUT THE BANK'S KNOWLEDGE - Firdaus, Amalina; Sativa, Annisa (JCH (Jurnal Cendekia Hukum), 2024)
The transfer of mortgage loans to third parties without the bank notice may result in losses between the bank and the third party. because in this process there must be approval from the bank as a creditor and is marked by an authentic deed as a reinforcement in this agreement. Therefore, this article aims to determine the validity of the private deed agreement on the transfer of mortgage loan credit without notification to the bank and the legal consequences of compensation for ownership of the object of mortgage loan credit after the private deed agreement of the transfer of the debtor. The research method used is normative juridical which is research that refers to legal norms and national laws, With a research approach (statute approach). The results of this study indicate that the transfer of a mortgage loan (KPR) to a third party without the bank's knowledge is null and void by law or invalid and the legal consequences arising from these actions, creditors and third parties can sue and request compensation from the debtor for defaulting, then for the third party who has received the transfer of the mortgage loan does not get a name change.